2021
DOI: 10.1016/j.msard.2021.102798
|View full text |Cite
|
Sign up to set email alerts
|

Fear and anxiety in patients with multiple sclerosis during COVID-19 pandemic; report of an Iranian population

Abstract: Background: There are reports that stress-related disorders are increasing during coronavirus disease 2019 (COVID-19) pandemic. Patients with Multiple Sclerosis (MS) are at higher risk of developing psychiatric disorders, which result in worsening of their disability. There are concerns about the mental health of MS patients during this pandemic. Objective: We aimed to evaluate the prevalence of anxiety, depression, and levels of fear about Corona in MS patients during the COVID-19 pandemic. Materials and meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 20 publications
4
33
0
Order By: Relevance
“…The COVID-19 pandemic was demonstrated to cause an increased level of anxiety and depression, and a worse sleep quality in MS patients throughout different countries [ 2 , 10 , 11 , 12 , 13 ]. The Italian authors of [ 14 ] reported a greater prevalence of severe stress (measured in PSS-10) in MS subjects, in comparison with the healthy controls or the patients with migraine.…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic was demonstrated to cause an increased level of anxiety and depression, and a worse sleep quality in MS patients throughout different countries [ 2 , 10 , 11 , 12 , 13 ]. The Italian authors of [ 14 ] reported a greater prevalence of severe stress (measured in PSS-10) in MS subjects, in comparison with the healthy controls or the patients with migraine.…”
Section: Discussionmentioning
confidence: 99%
“…emphasized that the COVID-19 pandemic causes depression in people with MS with a history of neuropsychiatric disorders, and elderly people with MS are more prone to anxiety. It was emphasized that anxiety was not present, especially in young and educated individuals ( Ramezani et al., 2021 ). The fact that individuals with COVID-19 disease have more fears and similar anxiety in our study can be attributed to the fact that the cases are young and have high academic backgrounds.…”
Section: Discussionmentioning
confidence: 99%
“…Anxiety might be an essential factor for this behavior, as this is frequently present in MS patients in the context of this pandemic. 7 In Germany, studies investigating the reason for patients to avoid hospital stays during the COVID-19 pandemic are lacking, but data from the USA confirm major concerns of people contracting another illness while being at a medical facility during the first wave of the COVID-19 pandemic. 8 Fear as the main driver is also supported by the dynamic of the observed decline seen from March 2020 on, when Germany faced the challenges of this pandemic for the first time, and the German government introduced the first-ever lockdown and strict hygiene measures for strong social distancing to control the spread of COVID-19.…”
Section: Discussionmentioning
confidence: 99%